2016
DOI: 10.1002/sdtp.11071
|View full text |Cite
|
Sign up to set email alerts
|

P-206L:Late-News Poster: QVGA AMOLED Displays Using the Carbon Nanotube Enabled Vertical Organic Light Emitting Transistor

Abstract: We present the first display panels exploiting the nVerPix CN-VOLET technology that reduces the pixel circuit of the conventional AMOLED display to two discrete components: the switching transistor and the CN-VOLET. This permits high aperture ratio bottom emission displays-as high as 70% hereand greatly simplifies the manufacturing. Mono-color QVGA AMOLED displays (6.4 cm diagonal) playing video will be shown. Author KeywordsOLED; organic light emitting transistor; carbon nanotube; active matrix P-206L / M. A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The year 2016 has seen the showcase at the same time of two distinct Active-Matrix OLET (AM-OLET) display prototypes at Society for Information Display Week in San Francisco (USA). ETC srl (Italy) [144] and NVerPix (USA) [145] have used a conventional planar OLET and a v-OLET to demonstrate active matrix addressing in red and green AM-OLET, respectively, on a mobile display size scale. Undoubtedly, this represents an important proof-of-principle of the potentials of the OLET platform in the field of active matrix display; nevertheless, a real implementation is yet to come.…”
Section: Discussionmentioning
confidence: 99%
“…The year 2016 has seen the showcase at the same time of two distinct Active-Matrix OLET (AM-OLET) display prototypes at Society for Information Display Week in San Francisco (USA). ETC srl (Italy) [144] and NVerPix (USA) [145] have used a conventional planar OLET and a v-OLET to demonstrate active matrix addressing in red and green AM-OLET, respectively, on a mobile display size scale. Undoubtedly, this represents an important proof-of-principle of the potentials of the OLET platform in the field of active matrix display; nevertheless, a real implementation is yet to come.…”
Section: Discussionmentioning
confidence: 99%
“…These key advantages assist in simplifying the device architecture that will lower the cost and open up promising opportunities for future flat panels and flexible display technologies. [29,58,59] In 2003, Hepp et al observed the light emission occurring near the edge of the drain electrode in a transistor device. [60] Following this work, research in OLET has gained attention and progressed slowly but steadily over the years with encouraging electrical and luminescent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, OLETs could be a key part of the development of next-generation AM display technology [29]. Indeed, a proof-of-principle device was recently developed using carbon nanotubes (CNTs, Figure 2), delivering a CNT-based vertical-type OLET (CNT-VOLET) [31][32][33][34]. In the CNT-VOLET, a dilute network of CNTs is used as a source electrode, leading to several improvements, such as a high on/off ratio, attributed to the gate-bias-induced modulation of the lateral (or horizontal) Schottky barrier height [31,32].…”
Section: Introductionmentioning
confidence: 99%